2020
DOI: 10.5195/jmla.2020.760
|View full text |Cite
|
Sign up to set email alerts
|

Grey literature citations in top nursing journals: a bibliometric study

Abstract: Objective: As access to information grows in tandem with the growth of the Internet, access to grey literature also increases. Because little is known about the use of grey literature in nursing journals, the authors investigated the prevalence and types of grey literature citations in top nursing journals.Methods: We analyzed all citations (n=52,116) from articles published in 2011 in 6 top nursing journals selected from the Medical Library Association’s Nursing and Allied Health Resource Section’s 2012 “Sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
(12 reference statements)
0
7
0
2
Order By: Relevance
“…Searches conducted by the first author between March and July 2020 were limited to peer‐reviewed journals, published in the English language between 2010 and 2020 (for decadal trend(s)) and availability of full text. Grey literature, accepted as print and electronic data, theses, and government, academic and business records that are not controlled by commercial publishers, helps to provide a more balanced review (Adams et al, 2016 ; Paez, 2017 ; Woods et al, 2020 ). Hand‐searching and Really Simple Syndication (RSS) feeds were used to alert newly published manuscripts from selected journals.…”
Section: Methodsmentioning
confidence: 99%
“…Searches conducted by the first author between March and July 2020 were limited to peer‐reviewed journals, published in the English language between 2010 and 2020 (for decadal trend(s)) and availability of full text. Grey literature, accepted as print and electronic data, theses, and government, academic and business records that are not controlled by commercial publishers, helps to provide a more balanced review (Adams et al, 2016 ; Paez, 2017 ; Woods et al, 2020 ). Hand‐searching and Really Simple Syndication (RSS) feeds were used to alert newly published manuscripts from selected journals.…”
Section: Methodsmentioning
confidence: 99%
“…Grey literature such as letters and editorials were not excluded. Woods et al (2020) found in a review of the bibliographies of nursing journals that the citation of grey literature was substantial, while Adams et al (2016) suggest that including grey literature in literature reviews is essential in some circumstances as the information may only be present in grey literature. Due to the critical realist philosophy underpinning this research and the potential to add meaningful data in the attempt to interpret the stratified reality, the search results were not limited to academic journals, and where possible, grey literature was included.…”
Section: Methodsmentioning
confidence: 99%
“…Another reason for including gray literature is that it is widely used. A recent study on nursing journals shows that gray literature accounts for about 10% of all citations [ 17 ], while another study showed that more than 10% of UK governmental publications in the field of health care are cited in the publication database Scopus [ 18 ]. Farrah and Mierzwinski-Urban [ 19 ] found that about 47% of the references on reports on novel nondrug health technologies were found in gray literature, and a review by Song et al [ 20 ] found that approximately half of all medical and health-related studies are not published in peer-reviewed journals.…”
Section: Introductionmentioning
confidence: 99%